A Review of the Processes Associated with the Removal of Oil in Water Pollution - Bradley Cerff (MDPI AG, 2021)
Water plays an essential role in production and refining processes. Many industries that use petrochemicals also require water, especially for cleaning purposes. The wastewaters released by these processes are often rich in petroleum pollutants, which requires significant treatment prior to disposal. The presence of petroleum contaminants in rivers and oceans is a significant threat to human health, as well as to many animal species. A current challenge for most industries and conventional effluent treatment plants is compliance with accepted disposal standards for oil-polluted wastewater. Of particular importance is the processing of dispersed oil in water, as well as oil in water emulsion. Conventional oil and water separation methods for processing oil in water contamination have several technology gaps in terms of applicability and efficiency. The removal and effective processing of dispersed oil and emulsions from oily wastewater is a costly and significant problem. The objective of this paper is to provide a review of the principles associated with oil in water emulsion separation, with the aim of providing a more definitive understanding of the terminology, processes, and methodologies, which will assist the development of a more efficient, innovative and environmentally friendly process for the separation of oily wastewater.